Differentiation of bovine mammary epithelial cells in the presence of linolenic acid in combination with thiazolidenediones - REZA, A M M T; LEE, S J; SHIWANI, S; SINGH, N K (The Indian Journal of Animal Sciences, 2017)
Cytoplasmic lipid droplets (CLD’s) formation is critical for lactation and health and so it could be detrimental in upholding the formation of CLD’s in bovine mammary epithelial cells (MAC-T). We therefore, treated MAC-T cells with differentiation medium containing alpha-linolenic acid (ALA) (100 μM) and thiazolidenediones (TZD’s) (10 μM) and observed CLD’s formation in cellular cytoplasm with Oil-red-O staining and elution index percentage. We also observed significant up-regulation of adipogenic and down regulation of epithelial markers. In conclusion, 100 μM ALA plus 10 μM TZD’s resulted in formation of CLD’s and subsequent differentiation of MAC-T cells.